ANALYSIS OF IMPLEMENTATION PSAK 72 ON REAL ESTATE COMPANY PERFORMANCE - Odagoma, Oswald Octaviano Orlando; Lindrawati, Lindrawati; Susanto, Adi (Jurnal Riset Akuntansi dan Keuangan, 2024)
Public companies in Indonesia use the Statement of Financial Accounting Standards (PSAK) as a standard for preparing financial reports. In 2020, PSAK 72 appeared which regulates contract income from customers. This research aims to analyze the performance of real estate companies before and after the implementation of PSAK 72. The sample are real estate companies listed on the Indonesia Stock Exchange for period 2018-2021 period which were selected using a purposive sampling method with The total sample is 59 companies. The data analysis technique used is a difference test using the Wilcoxon Signed Test. The research results show that there is a difference in financial performance before and after the implementation of PSAK 72 which is proxied by the current ratio, return on assets, return on equity, debt to equity ratio, and total asset turnover, but there is no difference if proxied by the debt to asset ratio. Meanwhile, in market performance, there is a difference in price book value before and after the implementation of PSAK 72 but there is no difference in the price earnings ratio before and after the implementation of PSAK 72.